ASSESSMENT OF THE IMAGE OF UKRAINE IN THE EUROPEAN MEDIA AT THE BEGINNING OF THE FULL-SCALE AGGRESSION OF THE RUSSIAN FEDERATION - Natalya Kharkevych; Zoriana Velychko (Інтегровані комунікації)
In the modern world, the media plays a key role in shaping the international image of states. Of particular note is the transformation of the perception of Ukraine in the European media in the context of the Russian-Ukrainian war, which became one of the defining events of modern history. The study analyzed how the image of Ukraine changed before and after the start of Russia's full-scale aggression on February 24, 2022. It emphasized how the heroism of the Ukrainian people, cultural resistance, and effective military defense influenced the change in attitudes towards the country in the international environment.